Asian and non‐Asian disparities in outcomes of non‐nasopharyngeal head and neck cancer. (11th April 2017) - Kim, Jason D.; Chang, Jennifer T.; Moghaddamjou, Ali; Kornelsen, Emily A.; Ruan, Jenny Y.; Olson, Robert A.; Cheung, Winson Y.
Abstract : Objectives/Hypothesis: To evaluate disparities in overall survival (OS) between Asian and non‐Asian patients diagnosed with non‐nasopharyngeal head and neck cancer (HNC). Study Design: This was a population‐based, retrospective study of patients diagnosed with non‐nasopharyngeal HNC of squamous cell carcinoma histology between 2001 and 2010 in British Columbia, Canada. Methods: Using Kaplan‐Meier methods and Cox regression models, we examined the relationship between race and OS. Results: A total of 3, 036 patients were included in the study. Median age was 64 years, 74% were men, and 7% were Asians. Asians had worse Eastern Cooperative Oncology Group (ECOG) status (29% vs. 23%, P = .07) and larger tumors (33% vs. 21%, P = .02), and were more likely to be diagnosed with oral cavity cancers (38% vs. 25%, P < .001) than non‐Asians. Asians were also less likely to receive multimodality therapy than non‐Asians (90% vs. 95%, P = .02). Asians were more likely to have never smoked (49% vs. 15%, P < .001) and to be married or with a partner (80% vs. 69%, P = .02). Multivariate models showed that Asians had better OS than non‐Asians (hazard ratio [HR] = 0.50, 95% confidence interval [CI] = 0.25‐0.99, P = .05). Three‐year OS did not differ significantly between Asians and non‐Asians (41% vs. 42%, P = .18); however, 5‐year OS did (22% vs. 19% P = .03). Stratifying by treatment type, outcomes were comparable in both groups except for radiotherapy alone, where Asians showed significantly better OS (HR = 0.71, 95% CI = 0.51‐0.99, P = .04). Advanced age, worse ECOG, greater tumor size, and lack of treatment also correlated with inferior OS. Conclusions: Despite several worse prognostic features and less aggressive treatment, Asians tended to exhibit better OS than non‐Asians. Level of Evidence: 2c. Laryngoscope, 127:2528–2533, 2017